Transmitter location estimation using software defined radio - Özşahin, Mustafa Tuğrul. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
This thesis focuses on the practical implementation of transmitter location estimation algorithms using software de ned radio devices for the purpose of radio environment map construction, which is used to determine primary user location and available channels for Cognitive Radio. To this end, a testbed is also set up and technical and physical details of this testbed are explained. Using the received signal strength (RSS) data collected from receivers with xed known locations, the path loss character of an open eld line of sight channel is estimated. Then, the location of an immobile transmitter is estimated using the collected RSS data from multiple receivers by applying one proposed and one known technique, and the results of these estimations are explained and compared. The e ect of receiver count and the environmental factors on the precision of the results are also explained. To share the gained experimental knowledge, the practical di culties, tradeo s, and experiences encountered during the implementation and measurement phases are explained.
Keywords: Software radio.